CHARACTERISTIC OF AMELOBLASTOMA IN ORAL AND MAXILLOFACIAL SURGERY AT HASAN SADIKIN HOSPITAL : 2 YEARS RETROSPECTIVE STUDY - Tanusantoso, Albertin Jane; Yusuf, Harmas Yazid; Sylvyana, Melita (Odonto : Dental Journal, 2021)
ABSTRACTBackground: Ameloblastoma is the most common odontogenic tumor. Ameloblastoma is a borderline tumor because it is a benign but locally aggressive tumor with a high recurrence rate if the excision is not complete. The principle of treatment for ameloblastoma is excision all the tumor. This article aimed to conduct a retrospective study to analyze the characteristics of ameloblastoma in patients at Oral and Maxillofacial Surgery Hasan Sadikin Hospital Oral Surgery between the period of January 2018-December 2019Method: This is a retrospective study with 37 patients diagnosed with ameloblastoma during 2018-2019. We took data from each patient such as gender, age, radiological features, histopathological diagnosis of the location of ameloblastoma, management, defects, reconstruction. Result: A total of 22 patients were diagnosed with plexiform ameloblastoma, 12 cases of follicular ameloblastoma, 3 cases of mixed plexiform and follicular ameloblastoma. 31 patients were treated radically, while 6 patients were treated conservatively. Radical treatment is more often used to reduce recurrence rates, whereas conservative measures are indicated in children and adolescents, as well as adult patients with unilocular ameloblastoma types. Conclusion: The most characteristic of ameloblastoma is plexiform ameloblastoma in the mandible. Ameloblastoma is usually performed radically and reconstructed with an AO plate.